2005
DOI: 10.1136/jnnp.2004.050286
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of preoperative high magnetic field motor functional MRI (3 Tesla) in glioma patients by navigated electrocortical stimulation and postoperative outcome

Abstract: The validity of 3 Tesla motor functional magnetic resonance imaging (fMRI) in patients with gliomas involving the primary motor cortex was investigated by intraoperative navigated motor cortex stimulation (MCS). Methods: Twenty two patients (10 males, 12 females, mean age 39 years, range 10-65 years) underwent preoperative fMRI studies, performing motor tasks including hand, foot, and mouth movements. A recently developed high field clinical fMRI technique was used to generate pre-surgical maps of functional h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
1
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(71 citation statements)
references
References 52 publications
1
68
1
1
Order By: Relevance
“…Bizzi et al 7 reported sensitivity and specificity of 88 and 87%, respectively, when hand motor function on fMR imaging was compared with ESM (both modalities were considered to match if fMR imaging activation was present within 1 cm of a positive ESM site). With similar criteria, Roessler et al 75 found 100% agreement in 17 patients with low-or high-grade gliomas. They were able to detect fMR imaging activation in the handknob region in all patients.…”
Section: Localization Of Primary Motor Areasmentioning
confidence: 99%
“…Bizzi et al 7 reported sensitivity and specificity of 88 and 87%, respectively, when hand motor function on fMR imaging was compared with ESM (both modalities were considered to match if fMR imaging activation was present within 1 cm of a positive ESM site). With similar criteria, Roessler et al 75 found 100% agreement in 17 patients with low-or high-grade gliomas. They were able to detect fMR imaging activation in the handknob region in all patients.…”
Section: Localization Of Primary Motor Areasmentioning
confidence: 99%
“…Their accuracy and specificity were discussed in recent studies. 1,28,36,37 Eloquent cortex that can be mapped using fMRI includes the primary motor and somatosensory regions, and Broca and Wernicke areas along with hemispheric language lateralization and their connectivity within the CNS by using DTI for displaying pyramidal, language, and visual tracts. 32,51 Intraoperative high-field (≥ 1.5-T) MRI systems are well established in operating rooms and were used in glioma surgery or frameless stereotaxy.…”
Section: Functional Mri Tractography (Dti) Neuronavigation and Imrimentioning
confidence: 99%
“…13,17,37 Additionally, white matter tracts can be detected ("fibertracking") by DTI and included in the neuronavigation, which we termed "multimodal navigation," 31 mainly to avoid awake craniotomies, which are cumbersome for the patient and surgeon.…”
mentioning
confidence: 99%
“…Moreover, cortical stimulation is a demanding, time consuming, and costly procedure and as such is often not possible during surgery. Therefore, because fMRI of motor and language tasks is feasible in patients with cerebral tumors (Mueller et al 1996), several groups have proposed the integration of functional data into the neuronavigation system in recent years (Krishnan et al 2004, Gralla et al 2003, Jannin et al 2002, Roessler et al 2005, Reithmeier et al 2003, Talos et al 2003, O'Shea et al 2006. And strong evidence that a more radical tumor resection may be achieved by using fMRI information during neurosurgery has been demonstrated by Krishnan et al 2004, Haberg et al 2004 Diffusion tensor imaging (DTI) has recently emerged as a potentially valuable tool for preoperative planning (Tummala et al 2004, Field et al 2004, Clark et al 2003, Wieshmann et al 2000, Moller-Hartmann et al 2002, Coenen et al 2003 and postoperative follow-up (Alexander et al 2003) of surgically treated brain tumors and vascular malformations.…”
Section: Introductionmentioning
confidence: 99%